Portfolio Strategies Evaluation in Developed Markets: A Sectoral Analysis of Minimum- and Mean-Variance Portfolios - El-Sabban, Mariam A. (AUC Knowledge Fountain, 2025)
This paper evaluates the performance of four fundamental economic sectors – energy, utilities, real estate, and the financial sector – in five advanced countries: the US, Canada, UK, Germany, and France throughout the period 2015 – 2024. It attempts to assess the best performing and most efficient sector-country combinations by applying time variant (dynamic) portfolio optimization frameworks, primarily the minimum-variance and mean-variance models. The study will present recommendations for investment policy that are based on risk-adjusted returns and empirical findings.